ANALISIS TANDA DAN MAKNA EKSPRESI TERKEJUT PADA DRAMA CURSED IN LOVE: Pendahuluan, Metode Penelitian, Hasil dan Pembahasan, Kesimpulan dan saran - i putu widiantara; Anak Agung Ayu Dian Andriyani (Universitas Negeri Padang, 2025)
This study aims to analyze the signs and meanings of surprised expressions experienced by the protagonist in the Japanese drama Cursed in Love. The research data consist of selected scenes from episodes 1, 3, 5, and 7 of the drama, which contain moments of intense emotional reactions and expressions of surprise. Data were collected using the observation technique by repeatedly watching the drama and taking notes of significant scenes. The data were then analyzed using a semiotic approach, applying Paul Ekman’s theory of basic emotional expressions (1971) to identify facial expressions of surprise, and Roland Barthes’ theory of denotation and connotation (1957) to explore the literal and cultural meanings behind the expressions. The analysis results are presented descriptively in an informal manner to make the findings easier to understand. The research shows that surprised expressions in Cursed in Love are not only universal emotional reactions but also carry deeper cultural and narrative meanings, such as trauma, distrust, and emotional tension, which reflect the character’s psychological development and family conflicts throughout the story. Keywords: Expression, sign, Meaning